Analisis Penggunaan Undangan Digital Dibandingkan Dengan Undangan Kertas Pada Acara Pernikahan Modern - Afrilia Herawati; Himmatul Aulia; Ika Syahputri; Lala Putri Amanda; M. Ihza Aulia Efendi; Noni Ardila Citra; Yuliana Yuliana; Zia Firjatullah; Try Santi Kisria Darsih (Journal of Innovative and Creativity, 2026)
The development of digital technology has brought significant changes in various aspects of society, including wedding ceremonies. One notable change is the shift from printed invitations to digital invitations. This study aims to analyze the comparison between digital invitations and printed invitations in modern wedding events in terms of cost efficiency, ease of distribution, effectiveness of information delivery, and environmental impact. This research uses a qualitative approach with literature study and observation methods. The results indicate that digital invitations offer advantages in cost efficiency, distribution speed, design flexibility, and environmental friendliness. Meanwhile, printed invitations still hold strong emotional and cultural values for some communities. The study concludes that digital invitations are more relevant for modern weddings, although printed invitations continue to play a role as symbols of formality and tradition.